Visualization of Gas Diffusion-Sorption in Coal: A Study Based on Synchrotron Radiation Nano-CT. (2nd July 2020) - Sun, Yingfeng; Zhao, Yixin; Zhang, Hongwei; Zhang, Cun
Abstract : Gas diffusion-sorption is a critical step in coalbed methane (CBM) exploitation and carbon dioxide sequestration. Because of the particularity of gas physical properties, it is difficult to visualize the gas diffusion-sorption process in coal by experimental methods. Due to the limitation of experimental approaches to image the three-dimensional coal pore structure, it is impossible to obtain the three-dimensional pore structure images of coal. As a result, the visualization of gas diffusion-sorption in coal pore structure by numerical ways is impossible. In this study, gas diffusion coefficients were firstly estimated by experiments. Then, a gas diffusion-sorption coupled model was developed which can be applied to the nanoscale geometry imaged by synchrotron radiation nano-CT. The dynamic process of gas diffusion and ad-/desorption in the nanoscale microstructure of coal was visualized by the developed gas diffusion-adsorption coupled model and the numerical simulation based on MATLAB. The simulation results show a good agreement with the experimental results. The gas diffusion-sorption coupled model and numerical method can help to investigate the effect of microstructure on gas diffusion and ad-/desorption and provides a possibility to investigate the multiscale gas transportation and adsorption in coal pore-fracture system.